TASTE AND OTHER SENSES: RECONSIDERING THE FOUNDATIONS OF AESTHETICS - Korsmeyer, Carolyn (The Nordic Journal of Aesthetics, 2018)
The sense of taste has served as a governing metaphor for aesthetic discernment for several centuries, and recent philosophical perspectives on this history have invited literal, gustatory taste into aesthetic relevance. This paper summarizes the disposition of taste in aesthetics by means of three stories, the most recent of which considers food in terms of aesthetics and its employment in works of art. I conclude with some reflections on the odd position that taste has achieved in the postmodern art world, and I make a case for the often unnoticed role that bodily senses have in the apprehension of art.